Evaluation of orofacial lesions relating child abuse, Esfahan, Iran: A quantitative approach - Firoozeh Nilchian; Leyli Sadri; Seyed Ebrahim Jabbarifar; Alireza Saeidi; Leila Arbab (Wolters Kluwer Medknow Publications, 2012)
Background: Family violence, including child abuse, neglect, and domestic violence, is a public health problem. The aim of this study was to provide data on prevalence and factors of Orofacial lesions relating child abuse in Iran to lend evidence to support preventing child abuse. Materials and Methods: The overall approach was a case-note review of children having child abuse note, recording by personnel of social services. Research ethical approval was sought from the Central social service organization. This study was conducted in Isfahan, Iran (2011). Result: The mean age of children, when abuse had been occurred was 8 years (SD = 1.68), and there were approximately an equal number of boys and girls. Children had a high physical experience (66.1%).Of these children, at least 60% sustained trauma to the face and mouth. Emotional abuse was 77.1%, neglect was 64.1%, and lower experience of sexual abuse which was 4.1%. There was a strong relationship between gender and abuser which shows girls have been affected by stepfathers (P = 0.001). Conclusion: Preliminary data suggest that there are strong evidence regarding the incidence of child abuse relating orofacial lesions which dentists should be aware of them. Future trials may draw on these useful baseline data to help their study design.